Resource Mobilization by Micro, Small & Medium Enterprises in India: An Exploratory Research - Mathur, Dhiraj (My University, 2026)
Micro Small Medium Enterprises (henceforth MSMEs) are the major drivers of the economies across the world. They not only are a major contributor to the GDP growth but also create employment for a major part of the population. Mobilization of resources is a key and critical strategy for MSMEs to sustain, grow and continue to contribute to the economy. However, due to limitation of their size, MSMEs face challenges of resource (human, financial, technology etc.) constraints. MSMEs also need to externally compete with Larger Enterprises (henceforth LEs) which by virtue of their vintage, market establishment, and better leverage of technology, deploy resources more effectively and efficiently. A detailed review of literature suggests that majority of work in resource mobilization has been conducted in LE setups. MSMEs differ from LEs in terms of capabilities to develop and execute strategies to manage and deploy resources for continued growth. These differences create unique challenges for resource mobilization in MSMEs. Hence, existing theories for LEs may not fully encapsulate and explain the uniqueness and nuances of resource mobilization in MSMEs. Further, due to significant differences in economic, political and social eco-systems between emerging economies such as India and developed economies, existing MSME theories developed for advanced economies may not map to those in emerging economies. A grounded exploration of resource mobilization by MSMEs in emerging economies is thus necessary for progressing research further on how MSMEs in emerging markets deploy resources in a resource constrained environment. This thesis aims to build a model around resource mobilization in MSMEs operating in India. We adopted an exploratory approach under which an iterative process of literature review was followed, highlighting the internal and external components and linkages of resource management and the dynamics of interaction between them. Based on literature review, we narrowed our focus to select resource management theories of Bricolage, Resource Orchestration and Social Embeddedness to build following research questions 1) How do various factors, internal and external to MSMEs, induce them towards Bricolage and what Bricolage actions do MSMEs utilize to sustain themselves? 2) How do MSMEs orchestrate resources internal and external to the organization to create competitive advantage? and 3) How do MSME leverage social network and embeddedness for mobilizing resources? An inductive, multiple-case research design was developed for the thesis. Data was collected from 6 MSMEs in India. Selection of organizations was done through theoretical sampling method. Data was collected and triangulated through semi-structured interviews, observations collected through field visits, documents such as financial reports provided by MSMEs, and data collected through secondary sources such as company websites. Data analysis was conducted through within case analysis and cross case analysis. The research thesis explores a hitherto less studied area of MSMEs within resource-scarce environments. This research would also assist MSME practitioners in emerging economies to plan for rapid resource mobilization and scaling up in their venture to achieve their objective of sustenance and growth under condition of resource scarcity. Finally, this research will also guide policymakers on what conducive and supportive conditions are needed to enable MSMEs to mobilize resources in emerging economies successfully.
Keywords: MSME; resources; resource constraints; resource mobilization; emerging economies